2020
DOI: 10.1016/j.ijwd.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of the burden of disease of atopic dermatitis using a smartphone research application, myEczema

Abstract: Background Our understanding of chronic diseases, such as atopic dermatitis (AD), could benefit from the ability to rapidly collect patient-reported, longitudinal data from a large population. Objective This study aimed to determine whether a smartphone app can be used to collect demographic and longitudinal symptom data and recognize prescribing patterns and affordability of medications to study the burden of AD. Methods We collected data us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Currently, there are no publications on the usability, acceptability, or impact of any of these apps in patients with AD or their caregivers, resulting in an inability to compare feasibility findings using our app to other available mobile health apps for AD. The most recent studies on mobile apps for AD focused on the burden of the disease as determined by itch score, quality of sleep, and energy or stress levels and involved a small number of users that precluded assessment of the clinical significance and impact of the app [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no publications on the usability, acceptability, or impact of any of these apps in patients with AD or their caregivers, resulting in an inability to compare feasibility findings using our app to other available mobile health apps for AD. The most recent studies on mobile apps for AD focused on the burden of the disease as determined by itch score, quality of sleep, and energy or stress levels and involved a small number of users that precluded assessment of the clinical significance and impact of the app [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few mobile app-based platforms currently exist for the conduct of dermatology clinical research. Review of the literature found reports of four apps developed for AD: one supporting caregivers of children with AD to improve disease self-management (10), an interventional app educating on AD and encouraging adoption of behavioral modifications (11), the myEczema app aiming to collect data on medication prescription/affordability and itch level in eczema patients (13,14), and a smartwatch app measuring nocturnal scratching in inflammatory skin diseases using accelerometer data (12). The SkinTracker system is distinct in comparison to these published solutions, as it collects a broader range of health behavior databoth active and passive, with validated survey tools and smartwatch biometric activity-and integrates patient-physician interactions (e.g., chat function, physician rating and calculation of EASI and IGA in photographs).…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest barriers to conducting remote dermatologic research is the lack of tools designed to collect patient data in a format that meets clinical research standards (10). With AD, a handful of digital applications (i.e., apps) have been published to help educate patients and manage their disease (10)(11)(12)(13)(14), but only one mobile app was specifically designed for clinical research purposes (14) and primarily collected itch severity ratings, coupled with a non-validated quality-of-life survey. In the clinical realm, the need for more comprehensive remote clinical monitoring tools for AD and other inflammatory skin diseases is particularly high, as patients often experience skin fluctuations or flares between in-person visits, meaning such encounters may not fully capture patients' clinical journeys while attempting new treatments (1).…”
Section: Introductionmentioning
confidence: 99%